2004
DOI: 10.1111/j.1460-9592.2004.01276.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of severe diazoxide toxicity

Abstract: Hyperinsulism is a rare cause of persistent hypoglycemia in the neonatal period. Therapy can be accomplished either surgically or pharmacologically. Diazoxide treatment remains the mainstay of medical therapy. Tolerance of diazoxide is usually excellent, but several adverse effects of this drug have been described. A case of severe diazoxide intoxication with fluid retention, congestive heart failure, and respiratory failure is reported. The patient was a 43-day-old infant, affected by persistent and severe hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 8 publications
(15 reference statements)
1
26
0
1
Order By: Relevance
“…The analysis revealed that the maximum dosage is the only factor for the overall incidence of complications associated with diazoxide. These findings are consistent with previous reports [14,19]. Infants who were administered diazoxide at more than 15 mg/kg/day showed a higher incidence of complications (76.4%) than those on less than 15 mg/kg/day (26.2%) (p < 0.05).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The analysis revealed that the maximum dosage is the only factor for the overall incidence of complications associated with diazoxide. These findings are consistent with previous reports [14,19]. Infants who were administered diazoxide at more than 15 mg/kg/day showed a higher incidence of complications (76.4%) than those on less than 15 mg/kg/day (26.2%) (p < 0.05).…”
Section: Discussionsupporting
confidence: 83%
“…In 2008, it was approved for the treatment of patients with HIH, and its use is considered to be expanding rapidly. Although the usefulness of diazoxide for HIH is well established [11], several life-threatening complications have been reported [12,13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…Prevalent complications, such as hypertrichosis, have also been proposed for diazoxide. Serious complications including pulmonary hypertension, heart failure and neutropenia (16), hepatomegaly, severe fluid retention, diffuse edema, congestive heart failure, and respiratory failure requiring mechanical ventilation (17) have also been reported. Another problem that exists in our country is the fact that diazoxide is not always available, due to sanctions.…”
Section: Discussionmentioning
confidence: 99%
“…Appart from acting as a diuretic, chlorothiazide has also direct β-cell pottasium channel opening activity. In a purpose to supply sufficient glucose, large volumes of intravenous fluids are infused to hyperinsulinemic infants and enhance the danger of severe water retention (Silvani et al, 2004). Somatostatin analogues are able to inhibit insulin secretion in various manners by inducing hyperpolarisation of β-cells, direct inhibition of the voltage-gated calcium channel and more distal insulin secretory pathways.…”
Section: Management Of Neonatal Hyperinsulinismmentioning
confidence: 99%